Fibroids with atypical presentation and related surgical challenges: case series - Khanam, Rosy; Hazarika, Bhaswati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Uterine fibroids refer to benign growth arising from uterus and are considered to be the most common gynaecological tumour mostly seen in women of reproductive age group. Myomas or uterine fibroids in majority may be asymptomatic and are diagnosed incidentally on imaging or on clinical examination. Significant morbidity can be caused by uterine fibroids by causing uterine bleeding, anemia, bulk symptoms and fertility issues. Quality of life can be severely affected in women with symptomatic fibroids. Uterine fibroids can be diagnosed early by ultrasound and magnetic resonance imaging (MRI). However, certain cases may present with unusual ultrasound and MRI reports causing diagnostic dilemma. Currently it is the most common indication for hysterectomy worldwide. We report 6 cases of uterine fibroids with atypical presentation with respect to location and features that caused diagnostic challenges and difficult surgeries that were performed at our institution.